A Case Report on Meropenem and Valproic Acid Drug-Drug Interaction Induced Status Epilepticus (Indian Journal of Forensic Medicine & Toxicology, 2023)
Valproic acid and meropenem is generally co-administrated in neurosurgical cases. Meropenem potentially decreases thevalproic acid position, which may beget perioperative turn like seizure. Such serious adverse effect through potential interactionshould be taken seriously and made aware by clinicians. Among various neurological emergencies status epilepticus is one ofthe most important and as it progresses, therapeutic control becomes difficult. Patients receiving antiepileptics and carbapenemgroup antibiotics concomitantly should be closely monitored due to possible drug interaction between these agents. Theauthors report a case of a 39-year-old male patient who was admitted with C4-C5 type C injury with neurological deficit dueto road traffic accident. His Glasgow Coma Scale score was E4M2V1 and graded ‘A’ on Asia Impairment Scale. Patient wason treatment with valproic acid for existing schizophrenia. He was empirically treated with meropenem as cover antibiotic forinfection due to phrenic nerve palsy that allowed secretions to be retained and increase the chance of infection. On third dayof admission, he developed 2 episodes of breakthrough seizure in less than 5 minutes. Post status epileptic, Inj. Meropenemwas stopped as cover antibiotic and he was treated with Inj. Fosphenytoin, Inj. Midazolam and Inj. Levetiracetam after whichno such seizures were observed.
Keywords: Meropenem, Valproic acid, Seizures and Drug interaction.